Pendampingan Dalam Penyelesaian Sengketa Tanah - Kartika Djuna; Novrilianty A Manuhutu; Masriawati Yuliana; Meske Patalatu; Arifin Rappe; Jabar Yahya (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Indigenous Village has duty to complete tasks that accur in the community so that the state government can help resolve community disputes, but the indigenous village also needs saniri in carrying out is function as a supervisor of the Indigenous village and competent institutions/agencies to resolve these disputes if they are resolved through non-litigation channels.Purposes of Devotion: The purpose of this paper is to provide assistance related of indigenous peoples’ land disputes and legal opinions, and socialization of clean justice. Method of Devotion: This Community Service Activity This research was conducted in Amahusu Country, Nusaniwe District, Ambon City. In this activity, several stages were carried out including (1) direct location observation and interviews with community leaders, intensive communication with the State Government and the State Saniri Amahusu. (2) identification is carried out by examining the Profile of Amahusu Country specifically to find out the problems that occur in Amahusu Country. (3) Taking solution steps.Results of the Devotion: After carrying out this service activity, it was found that disputes that often occur in Amahusu Country are land disputes of indigenous people, dispute resolution in the view of the community can be resolved by the Indigenous Village, however, not all disputes can be resolved by the Indigenous village, so competent institutions/agencies are needed to resolve disputes that occur in the community. Dispute resolution can be done through non-litigation channels in the form of mediation, in addition to litigation. In addition, the public has a lack of trust in law enforcement officers, so socialization is needed to restore public trust in law enforcement officers.